PENGARUH TQME, GAYA KEPEMIMPINAN DAN KEDISIPLINAN KERJA TERHADAP KINERJA DOSEN: Studi pada Perguruan Tinggi Swasta di Jawa Timur - Iliyawati, Wachidatuz Zuhria (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2016)
This study aim to examine influence of Total Quality Management in Education, Leadership and Labore Dicipline to Lecture Performance. Using a survey sample colected from 144 lecture who have worked at Privat University in East Java. This study was done using computer delivered surveys, mail surveys and pick up surveys data collection. The finding of the study reveal that labore dicipline has a significant influence on the lecture performance and TQME, leadership has not significant influenceon the lecture performance.The result of this study profide the conclusion that adoption of TQME and leadership will not increase lecture performance and labore dicipline will increase lecture performance.